The failure of democratic nation building ideology meets evolution - Somit, Albert; Peterson, Steven A. (Palgrave Macmillan, 2005)
Democracy requires very special 'enabling conditions' before it can be supported by a state, conditions that require decades to evolve. As a result, attempts to export democracy through nation-building to states without these enabling conditions are doomed to failure